2012
DOI: 10.1007/s00231-012-0986-x
|View full text |Cite
|
Sign up to set email alerts
|

Double tube heat exchanger with novel enhancement: part II—single phase convective heat transfer

Abstract: The study is conducted to evaluate the heat transfer characteristics of two new and versatile enhancement configurations in a double tube heat exchanger annulus. The novelty is that they are usable in single phase forced convection, evaporation and condensation. Heat transfer coefficients are determined by the Wilson Plot technique in laminar and turbulent flow and correlations are proposed for Nusselt numbers. Comparisons are then made between heat transfer and flow friction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The experimental procedure for determination of condensation characteristics utilizes results from earlier investigations of the authors [1,2]. Hence it is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental procedure for determination of condensation characteristics utilizes results from earlier investigations of the authors [1,2]. Hence it is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These correlations are then used to extract the condensation heat transfer coefficient from the overall condensation process where phase change of the refrigerant occurs from superheated vapor to subcooled liquid. The correlation for the single phase heat transfer coefficient has been obtained in Tiruselvam and Raghavan [2]. From the initial analysis of the current experiments, it was found that the flows of both superheated vapor and subcooled liquid in the annulus are in the turbulent flow region.…”
Section: Overall Average Heat Transfer Coefficientmentioning
confidence: 96%
See 3 more Smart Citations